Arterial hypotension in patients with essential hypertension II–III: unresolved issues and ambulatory blood pressure monitoring diagnostic criteria - V. V. Syvolap; S. P. Zhemaniuk; Yu. O. Maliarenko (Zaporožskij Medicinskij Žurnal)
The aim was to study the prevalence of sustained arterial hypotension in high cardiovascular risk patients with II–III stage essential hypertension and associated factors.